The domestic space and its (dis)order in the theater of Sophocles - Obrist, Katia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
Many tragedies confer a central place on the domestic institution: their plots develop the tensions into the oíkos and show its destabilization (Gambon, 2009: 45). The palatial structure is another factor because, as a backdrop, it visually connects the audience with the inside off-stage and endorses the game of recognition and distance in time and space which is typical to the tragic work. The discursive and visual construction of the private sphere that occurs in the tragedies is, therefore, an aspect that we need to study in depth. Furthermore, it is the tragic problematization of a social imaginary, which assigns their domain to each sex and displays qualities conceived as innate with the purpose of maintaining social stability. Based on these considerations, a register of the most frequent terms relating to the private area within the Sophoclean corpus is attempted. I work with the tragedies preserved which suggest its presence: Trachiniae, Antigone, Oedipus Tyrannus and Electra. Furthermore, in a second scan a look at the terms that refer to the central door is presented. I observe whether there is a preference for expressions with lexical content, which point to the home and the door, or for deictic terms. Finally, I propose another variable in these scans, which attends to the enunciator of each expression, in order to explore the tendencies in their use in accordance with gender and social class.
Keywords: Sophocles; domestic space; door; woman